DRAW.IN.G.: A tool to explore children’s representation of the preschool environment - Berti, Sara; Cigala, Ada (Frontiers in Psychology, 2022)
The use of drawing as a research tool has often been the subject of debate in the field of developmental psychology, especially for the exploration of children’s meanings on a specific topic. Methodological limitations do emerge when using drawing in research, especially in preschool age. One of the main critical aspects concerns the lack of systematic and standardized coding methods that include clear and operationalizable categories to analyze the content of the drawings, and that associate a brief interview with the children aimed at avoiding misinterpretations. To bridge this gap, the present contribution introduces a new methodological tool named DRAW.IN.G. (DRAWing and Interview Grid), consisting of a specific procedure and a coding system that allow for a systematic investigation of implicit and explicit levels of children’s representation emerging via drawings and interviews. The specific topic investigated by DRAW.IN.G. is children’s representation of the preschool environment; the scarcity of studies on this issue, despite the importance of including children’s point of view in the design processes of educational spaces makes the tool particularly current and relevant to fill some gaps in research in the educational field. The DRAW.IN.G. coding system, developed on the basis of existing literature on the analysis of drawings, includes five main dimensions of children’s representation of the educational environment: physical, behavioral, relational, emotional and motivational dimensions, articulated in 18 macro-categories and 90 categories that make up the scoring grid. To assess the validity of the method, a first application was conducted with a sample of 262 children (141 males, 121 females; mean age = 55.78 months; SD = 11.10; range 37–77 months) from five Italian preschools. Categorical inter-rater reliability of two independent raters showed good to excellent agreement for the categories of the grid, indicating their appropriateness and clarity. The validation study indicated the potential of the method, also revealing some critical aspects to be considered. Both methodological and practical implications are discussed.